IMPLEMENTASI MODEL PEMBELAJARAN MATEMATIKA BERINTEGRASI KEISLAMAN DALAM MENINGKATKAN KARAKTER DEMOKRASI SISWA - nani fitriah; Arif Muchyidin; jamali sahrodi (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2015)
Mathematics is not only as science that emphasize the cognitive ability, moreover in the attitude establishment and good behavior, while in learning mathematics teacher usually, only emphasizes cognitive ability and teacher seldom to pay attention about students’ so character is still low, on of them is students’ democratic character. Students’ democratic character is still low, it can be showed that they don’t ask to understand the lesson. So, it is needed the effort to improve studnts’ democratic character, that is implementation of Islamic Integration Model in liearning mathematics. The fuction of research are 1) to find out the students’ democratic character by using Islamic integration model in learning mathematics. 2) to find out the students’ democratic character without using Islamic integration model in learning mathematics. 3) to find out the implementation the Islamic integration model in learning mathematic on students’ democratic character better than the convensional model in learning mathematic. Variabel of this research is students’ democratic character, especially in learning mathematics with the theme tangent circle. The research method used is a quantitative method by using quasi eksperimental design. Techniques of collecting data of this research are attitude scale, observation, and interview. Population in this research is the eighth grade students’ of MTs NU Putri 3Buntet Pesantren Cirebon Year 2014/2015 about 213 students. Sampel of the research is cluster random sampling, it can be done by choosing group of two class that is grade of VIII D as experimental class and grade of VIII E as control class. The analyisis data is using descriptive statistic and inferensia statistic. The result of this research can be concluded that 1) students’ democratic character in experimental class when learning mathematics by using Islamic integration model in the good categorization is showed by number of attitude scala is about 83%; 2) students’ democratic character in control class when learning mathematics without by using Islamic integration model in the good categorization is showed by number of attitude scala is about 68%; 3) descriptively, students’ democratic characterexperimental classtend to be higher than control class, but thestatistical result not significant because the score of significant about 0,06. It shows not different of students’ democratic character learning mathematic by using Islamic integration model and conventional model significant standard = 5%.Key words : Islamic Integration, Democratic Character